PENGEMBANGAN PERANGKAT PEMBELAJARAN SAINS BERORIENTASI PADA SIKLUS BELAJAR 5E UNTUK MEMBERDAYAKAN KETERAMPILAN BERPIKIR DAN PEMAHAMAN KONSEP SISWA SMP - Laras Firdaus; Muslimin Ibrahim; Rudiana Agustini (Bioscientist : Jurnal Ilmiah Biologi, 2014)
This study aims to develop science-oriented learning devices oriented to a decent 5E learning cycle to empower the thinking skills and understanding of the concept of junior high school students. The development of the tool is based on the Dick & Carey development model (2009), and is implemented in the seventh grade students of SMPN 3 Satap Pringgabaya, East Lombok, by using one group pre-test and post-test design. Based on the research that has been done, there are some findings that is, the value of learning learning device validity ranges from 3 - 4, the average has good category, and the reliability of learning devices developed ranges between 90.84% - 98.83%. The lessons that have been implemented have good category, the students enthusiastically follow the learning activity, the level of legibility of the textbook developed at the instructional level, the most dominant activity done by the students during the activity is measuring, observing and / or doing practicum, working on LKS, and answer (give) responses. Learning cycle 5E has been implemented is a new learning model for students, students feel happy with the 5E learning model, because it can empower the thinking skills and understanding of student concepts, and the average level of thinking and understanding of students are at the relational level, with a percentage of 45.67%. Based on the results of research that has been implemented, it can be concluded that, learning tools developed feasible, practical, and effective, so it can be applied to empower the skills of thinking and understanding of concepts.